SIKAP DAN KEPUASAN KONSUMEN TERHADAP PEMBELIAN SATE DI KOTA BANDAR LAMPUNG - Lika Oniaranti Sitorus; Ktut Murniati; Kordiyana K Rangga (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
The study aims to analyze consumer attitudes, consumer satisfaction and the influence of consumer attitudes and satisfaction to the purchase of satay. Data were collected in June–July 2018. The research location is determined purposively with the consideration that the LWS and HJA Restaurants were established in the same year but they have different business development. There are 60 respondents collected using accidental sampling. The analytical methods used are Fishbein Multi-attribute Analysis and Customer Satisfaction Index (CSI). The results showed that consumers of LWS and HJA Restaurants have attitude of trust in products and service attributes. Consumers feel very satisfied with the purchase of satay at LWS and HJA Restaurants. The majority of consumers kept buying satay at LWS and HJA Restaurants even though the price of satay increased. Key words: attitude, consumer satisfaction, satay